Payments for ecosystem services in Indonesia. Issue 3 (20th June 2016) - Suich, Helen; Lugina, Mega; Muttaqin, Muhammad Zahrul; Alviya, Iis; Sari, Galih Kartika
Abstract: Payments for ecosystem services schemes are viewed as having the potential to achieve positive biodiversity and ecosystem service outcomes and social outcomes, and they have been widely studied since their development in the 1990s. We describe the state of payments for ecosystem services in Indonesia, where nine schemes were identified, four involving water and five involving carbon. We also assess the perceptions of stakeholders (donors, government, and non-government agencies) regarding the status of such schemes in Indonesia, and their views on what factors support or constrain their development. The main factors perceived to support payments for ecosystem services schemes were easily identifiable ecosystem services and service users, and the long-term support provided by individuals or institutions that facilitate the schemes, building on existing relationships between communities and these facilitating agencies. Stakeholders identified problems relating to regulation: the lack of regulation specifically in relation to payments for ecosystem services, but also overlap and uncertainties regarding regulations. Other constraining factors identified were the lack of recognition of environmental problems amongst potential buyers, and issues of rights and tenure for local communities. With so few operational programmes to date, covering a relatively small land area, and such constraints to further development, payments for ecosystem services schemes appear to have limited scope to supply ecosystem services successfully and sustainably at scale.